The Relationship between the Brexit Vote and Individual Predictors of Prejudice: Collective Narcissism, Right Wing Authoritarianism, Social Dominance Orientation - Golec de Zavala, Agnieszka; Guerra, Rita; Simão, Cláudia (Frontiers in Psychology, 2017)
The Leave campaign in the U.K., which advocated exiting the European Union, emphasized anxiety over immigration and the need to take control of the U.K.’s borders. Citizens who expressed concerns about immigration to the U.K. were more likely to vote to leave. Two correlational studies examined the previously unexplored question of whether the Brexit vote and support for the outcome of the E.U. referendum were linked to individual predictors of prejudice towards foreigners: British collective narcissism (a belief in national greatness), right wing authoritarianism and social dominance orientation. The results converged to indicate that all three variables were independently related to the perceived threat of immigrants and, via this variable, to the Brexit vote and a support for the outcome of the E.U. referendum. These variables explained the variance in the perceived threat of immigrants and support for the Brexit vote over and above other previously examined predictors such as age, education or ethnicity, as well as, national identification and national attachment.